Takayasu Arteritis and Pregnancy. Issue 12 (25th November 2015) - Comarmond, C.; Mirault, T.; Biard, L.; Nizard, J.; Lambert, M.; Wechsler, B.; Hachulla, E.; Chiche, L.; Koskas, F.; Gaudric, J.; Cluzel, P.; Messas, E.; et al.
Abstract : Objective: To assess the relationship between Takayasu arteritis (TAK) and pregnancy outcome. Methods: This study included 240 pregnancies in 96 patients fulfilling the American College of Rheumatology 1990 criteria for the classification of TAK and/or the 1994 Chapel Hill Consensus Conference nomenclature/criteria for vasculitis. We analyzed obstetric and maternal outcomes in women who were pregnant before and/or at the same time as or after TAK diagnosis. We assessed factors associated with complicated pregnancy. Results: One hundred forty‐two pregnancies occurred in 52 patients before TAK diagnosis (median age at pregnancy 26 years [interquartile range 23–30 years]), and 98 pregnancies occurred in 52 patients concomitant with or after TAK diagnosis (median age at pregnancy 28 years [interquartile range 26–31 years]). Pregnancies concomitant with or after TAK diagnosis had a 13‐fold higher rate of obstetric complications compared to pregnancies before TAK diagnosis (odds ratio 13 [95% confidence interval 5–33], P < 0.0001). TAK was associated with a 40% frequency of obstetric complications, including preeclampsia/eclampsia (24 pregnancies [24%]), premature delivery (8 pregnancies [8%]), and intrauterine fetal growth restriction or death (5 pregnancies [5%]). Maternal complications of TAK occurred during 39% of pregnancies and included mainly new‐onset or worsening hypertension (26 pregnancies [27%]). In multivariate analysis, smoking (odds ratio 6.15 [95% confidence interval 1.31–28.8]) and disease activity of TAK (a National Institutes of Health score of >1) (odds ratio 28.7 [95% confidence interval 7.89–104.7]) were independently associated with obstetric and maternal complications. Conclusion: TAK negatively affects pregnancy outcomes. Disease activity increases the risk of obstetric and maternal complications, mainly due to arterial hypertension.